1999
DOI: 10.1038/19104
|View full text |Cite
|
Sign up to set email alerts
|

The motor protein myosin-I produces its working stroke in two steps

Abstract: Many types of cellular motility, including muscle contraction, are driven by the cyclical interaction of the motor protein myosin with actin filaments, coupled to the breakdown of ATP. It is thought that myosin binds to actin and then produces force and movement as it 'tilts' or 'rocks' into one or more subsequent, stable conformations. Here we use an optical-tweezers transducer to measure the mechanical transitions made by a single myosin head while it is attached to actin. We find that two members of the myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
253
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(270 citation statements)
references
References 23 publications
17
253
0
Order By: Relevance
“…If d = 5.5 nm is an underestimate, and is equal to 10 nm under high calmodulin concentrations (21), the duty ratio is ∼0.5 at 1 pN and > 0.8 at 2 pN ( Figure 8). Although this simulation is a rough estimate of the force-dependence of the duty ratio, it supports the proposal that myo1b (and likely myo1a and myo1c) are motors well designed for tension maintenance and tension sensing (10,13,35,39). It is interesting to note that alternative splicing within the myo1b lever arm results in isoforms with four, five, or six IQ motifs, and thus may be a mechanism for tuning the strain-dependence of the myo1b duty ratio (21).…”
supporting
confidence: 77%
“…If d = 5.5 nm is an underestimate, and is equal to 10 nm under high calmodulin concentrations (21), the duty ratio is ∼0.5 at 1 pN and > 0.8 at 2 pN ( Figure 8). Although this simulation is a rough estimate of the force-dependence of the duty ratio, it supports the proposal that myo1b (and likely myo1a and myo1c) are motors well designed for tension maintenance and tension sensing (10,13,35,39). It is interesting to note that alternative splicing within the myo1b lever arm results in isoforms with four, five, or six IQ motifs, and thus may be a mechanism for tuning the strain-dependence of the myo1b duty ratio (21).…”
supporting
confidence: 77%
“…A group of myosins (similar to those with the ADP induced tail swing) have been shown in the elegant work of Veigel et al (1999Veigel et al ( , 2002Veigel et al ( , 2003, to exhibit a double step in the laser trap, single molecule displacement measurements. These two steps have been interpreted to reflect a displacement step associated with P i release and a second (usually smaller) displacement step associated with ADP release.…”
Section: Double Step In the Optical Trapmentioning
confidence: 99%
“…Using a single-molecule technique, Veigel et al (1999) have recently found that the working stroke of certain slow, non-muscle myosins consists of two well-separated steps, each of about 5 nm. When they used subfragment S1 of skeletal muscle, they could not fully resolve two steps in the attachment but showed that it occupied some 5 ms as against 1ms for detachment, suggesting strongly that it too consists of more than one step.…”
Section: Number Of Attached Statesmentioning
confidence: 99%